Cat Kid comic club. Perspectives - Pilkey, Dav, 1966- (Graphix, 2021)
As Flippy, Molly, and Li'l Petey try to manage their class of twenty-one baby frogs, they teach them cool comic-drawing tips and how to appreciate others with different perspectives.